The Using Benchmarking techniques in brand development of agriculture and tourism destination in Nakhon Pathom province - Tanyong, Phongsan; Sirinthanathon, Natasha (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The aim of this research were to study tourist behavior of buying in agricultural product and tourism destination of Nakhon Pathom province and to benchmark the five favorite brands of agricultural product and tourism destination of Nakhon pathom province compare with competitors. The results indicated that the five favorite brands of agricultural product of Nakhon Pathom province were pamelo, sticky rice in bamboo, pork, coconut jelly and processed pork. The five favorite brands of tourism destination were Pra Pathom Chedi,Wat Rai khing , Rose garden, Don wai riverside market and Snam Chan Palace. The benchmarking found that agricultural product that had competitive advantages was the pamelo and tourism destination that had competitive advantages were Wat Rai khing , Rose garden and Don wai riverside market. Article history : Accepted 12 March 2014 SIMILARITY INDEX = 0.00